(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
طُورت طريقة طيفية سريعة، اقتصادية و سهلة التطبيق، دقيقه و حساسه لتحديد الافلوكساسين (OFX) في حالته النقية وفي مستحضراته الصيدلانية باستخدام كاشف 2-امينو-6- نترو بنزوثيازول (ANB). تعتمد هذه الطريقة على تشكيل معقد أصفر برتقالي اللون عند pH =5.2، و درجة الحرارة 80±5 ºC خلال زمن قدره خمس دقائق. يمتلك المعقد المتشكل قمة امتصاص أعظمية عند طول الموجة 440nm . كانت العلاقة ما بين الامتصاصية وتركيز (OFX) طردية خطية وتحقق قانون بيير ضمن مجال التراكيز 1.80-86.72µg/mL، وبانحراف معياري نسبي مئوي لم يتجاوز±2.54% مع معامل ترابط 0.999، وبلغ معامل الامتصاص الجزيئي(L.mol-1.cm-1) 3.952×103. استخدمت هذه الطريقة بنجاح في تحديد الافلوكساسين بشكله النقي وفي المستحضرات الصيدلانية وتم التحقق من صحة النتائج إحصائياً ، ودلت النتائج على أن الطريقة المطورة ذات دقة وحساسية عاليتين. A Simple, accurate and highly sensitive spectrophotometric method have been developed for the rapid determination of Ofloxacine (OFX) in pure form and pharmaceutical formulations. The visible spectrophotometric method was based on the formation of a Orange Yellow colored complex between the (OFX) and 2-amino-6-nitrobenzothiazole (ANB) at pH 5.2 and 80±5 ºC in 5 min., and λmax at 440 nm. The effects of analytical parameters on the reported system were investigated. Beer’s law was obeyed in the concentration range of 1.80-86.72 μg/mL, with a percentage relative standard deviation not exceed ±2.54 and the molar absorptivity coefficients was 3.952×103 (L/mol.cm). Interferences of the other ingredients and excipients were not observed, the results showed that the developed method with the accuracy and sensitivity highs